O balançar da rede: turismo comunitário da Rede Tucum no Facebook - Silva, Fernando José Sousa da (2015)
Tourism is an important economic activity in Brazil. It is seen as inducer of social inclusion, development, generating employment and income. However, its standard organization cause social and environmental impacts without generating development. In contrast to this type of tourism, some organized groups propose alternative models. Among them, is the Community-based tourism, whose basis lies in the mobilization of the collective potencial of theses groups for the defense and the maintenance of their land and heritage. Tourism is understood here as a practice of consumption and entertainment anchored in leisure with strong communicational aspect. As concern to communication, it's understood as a process of interaction and building relationships. This dissertation analyzes the communication and promotional strategies of the community-based tourism on the coastal area of Ceará. The focus of this work is the Rede Tucum - Rede Cearense de Turismo Comunitário on Facebook. The site is, nowadays, one of the biggest sites of social networking in users numbers. Also, it's a important tool for Rede Tucum to communicate with its members and to promote the comunnity-based tourism. The observation and subsequent analysis of the actions of Tucum on Facebook focus on four axs: the coexistence in the site of a profile and a web page, the communities albums, the use of hashtags and the contents published by Tucum. The analysis of Tucum's page and profile aims to identify if there are differences in their uses. About the albums, the focus will be on those dedicated to introduce the communities. The intention is to investigate if those album are performing the function of introducing the communities to potential travelers. The observation of the use of hashtags seeks to identify whether the Rede Tucum uses it in their publications, and if the answer is positive, what are the terms used and to that they are related. About the publications on Tucum's page, will seek to discern themes it ponders and shares in its time line. The research identified the need for the construction of a communication policy for the Rede Tucum so that it can give cohesion to its actions of communication and promotion of the community-based tourism.